The Criteria of Political Leaders Assessment Obtained by Repertory Grids - Lutsenko, Olena; Kyrylenko, Ganna (Psychological Prospects Journal, 2016)
This article presents the results of the study of the voters assessment criteria of political leaders obtained from the application of a psychosemantic analysis using the method of Kelly’s repertory grids. This method has allowed to determinate rank of various interpretative statements by which voters describe and assess politicians. The results include the main assessment criteria used by voters towards politicians by the generalization of interpretive constructs. It was fond that following criteria have the greatest importance: “Political qualities” and “Moral qualities”. The voters describing political qualities use mostly constructs about status of leaders, but do not describe his/her qualitative characteristics. It was found also that most of the constructs used in the description of the moral qualities of politicians have a negative connotation. The analysis of the constructs revealed high importance of the time criterion. Due to the statuses attributed to politicians by voters, it was revealed that voters clearly classify politicians into the “new”, “ruling” and “old” powers. They are characterized by the following features: the politicians of the “new power” are associated with the future, they are credited with more positive moral qualities; the politicians of the “ruling” power have an ambivalent attitude; and the politicians the “old” power are associated with the past, they are credited with negative moral qualities. Constructs, which are an expression of aggression and aversion towards political leaders, were grouped in a separate assessment criterion. The criteria with the lowest weight in the political leader assessment were determined. They were sex, economic and territorial criterion. Results of the study presented in the article indicate stereotypeness inherent in modern voters, primitive idea of the role of leaders in the political life. Descriptions of politicians are formatted, conventional; they do not practically include definitions of political orientation: democratic, conservative, authoritarian, etc. Keywords: assessment criteria, political leaders, constructs, psychosemantic methods, voters.